Rare Variants Residing in Novel Cis-Acting Element in Visual System Homeobox 1 and Their Contribution in the Pathogenesis of Keratoconus - Farhan Khashim Alswailmi; Rida Khursheed Malik; Mujeeb Ur Rehman Parrey; Abdul Rauf Siddiqi; Shaik Karimulla; Abdulkareem A. Alanezi; Raheel Qamar; Maleeha Azam; Ashfaq Ahmad (Applied Sciences, 2023)
(1) Background: The visual system homeobox 1 (VSX1) may contribute to the incidence of keratoconus (KC) in different populations. The present study investigated the role of VSX1 in autosomal recessive Pakistani families and sporadic KC patients using in silico analysis of the rare variants for the identification of the cis-acting elements in VSX1; (2) Methods: Mutation analysis of VSX1 was undertaken using Sanger sequencing of samples from seven KC families and 100 sporadic patients. In silico analysis of the rare variants and identification of cis-acting elements was determined using Human Splicing Finder (HSF), ESE finder, RESCUE-ESE and through Exon- Identity Element (EIEs) prediction software suits, combined with various algorithms to identify the effect of variations in splicing motifs; (3) Results: Screening of VSX1 did not reveal any novel mutation in the KC panel, but a synonymous polymorphism rs12480307 (c.546A>G; p.Ala182Ala) in exon three and 3′UTR rs76499395 (c.*496A>G) were observed in two separate probands. These polymorphisms were not found in any of the sporadic KC cases or 100 ethnically matched control samples. The analysis of these rare variants revealed a plausible role for these two single nucleotide polymorphisms (SNPs) in KC development through the identification of novel cis-acting elements, an exonic splicing enhancer element (ESE) and binding motifs for two micro RNAs, miRNA-203 binding and hsa-miR-3938, in the VSX1 gene structure; (4) Conclusions: Rare genetic variations in the VSX1 were found to have a potential contribution to KC development.